Earth Science Education Research in the Philippines: Insights from Published Scholarly Work (2013–2022) - Christoper Jan B. Landicho (Jurnal Penelitian Pendidikan IPA, 2025)
Addressing many of today’s global challenges requires solid understanding of the different geologic processes that operate in and shape our planet. As such, Earth science has been included in the national science standards of many countries, including the Philippines. To describe the status of scholarly work in this discipline, one can draw insights from the systematic analyses of published research outputs, such as journal articles. This paper presents the state of research on Earth science education in the Philippines from 2013 to 2022. Google Scholar searches and a survey of locally published journals yielded 28 open-access research papers for analysis. Inclusion criteria were based on previous bibliometric studies conducted in other subfields of science education. Data collection was accomplished from January to November 2024. Most research studies focus on learning conceptions and adopt a quasi-experimental research design. The most frequently investigated demographic group are high school students and sample sizes vary from 30 to more than 500. Researcher-made tests and questionnaires were widely used as data collection tools, while inferential statistical methods were commonly utilized in data analysis. Implications to Earth science education research and recommendations to expand the scope of similar studies in the future are also discussed.